Toward Regional Low-Carbon Energy Transitions in England: A Relational Perspective - Crowther, Ami; Petrova, Saska; Evans, James (Frontiers in Sustainable Cities, 2021)
Re-scaling energy systems and governance to the local level is increasingly necessary to transition to a low-carbon society. City region devolution in England enables city regions to develop their own approaches to low-carbon transitions that reflect the context in which they are situated. The approaches associated with these transitions support the localization of the energy system, the involvement of a diverse range of actors and institutions and the establishment of new supporting infrastructures. This paper considers the interactions between, and influence of, different actors, infrastructures and institutions and how these impact the nature of approaches developed by applying a relational perspective. Relational perspectives are increasingly prevalent in research on low-carbon transitions, although they have not been used to consider how different components of the transition influence the approaches developed—which is the focus of this paper. By understanding the influence of the different components, it supports the establishment of appropriate mechanisms to facilitate low-carbon transitions at the localized scale. This paper analyses the approaches to low-carbon transitions developed by three city regions with devolved powers in England. The approach developed by each of the city regions orientates around a different scale of focus—from the whole city region to strategic hubs to individualized, siloed activity. These different scales of focus reflect the influence held by the actors, institutions and infrastructures located within each city region. The context of the city region itself also influences the actors, institutions, and infrastructures present. By adopting a relational perspective, it unpacks the complex interrelations, the multiple points of interaction and influence, and the multi-scalar nature of low-carbon transitions at the city region level. Although the approaches to low-carbon transitions developed by the different city regions suggest a re-scaling of transition processes, the associated actors, infrastructures and institutions associated with these processes are not isolated from broader contexts and particularities of place. There are multi-scalar interactions and influences which impact the nature of approaches developed, demonstrating the value of relational and heterogeneous perspectives when developing localized approaches to low-carbon transitions.